The two geodesic equations are:

$$\frac d{ds} (Eu' + Fv') = 1/2(E_u {u'}^2 + 2F_u u'v' + G_u {v'}^2) $$

$$\frac d{ds} (Fu' + Gv') = 1/2(Ev{u'}^2 + 2F_v u'v' + G_v{v'}^2) $$

And in the hyperbolic plane $H^2$, $E=G=1/y^2$, $F=0$. Put them into the first geodesic equation, I can get two solutions: $x=\text{const}$ and $(x-a)^2+y^2=c$, which are just the geodesic in $H^2$. But is that true that we can get the geodesic only by the first geodesic equation? Thank you.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.